2022
DOI: 10.1080/15592324.2022.2106410
|View full text |Cite
|
Sign up to set email alerts
|

ROS and calcium oscillations are required for polarized root hair growth

Abstract: Root hairs are filamentous extensions from epidermis of plant roots with growth limited to the apical dome. Cell expansion undergoes tightly regulated processes, including the coordination between cell wall loosening and cell wall crosslinking, to form the final shape and size. Tip-focused gradients and oscillations of reactive oxygen species (ROS) together with calcium ions (Ca 2+ ) as indispensable regulated mechanisms control rapid and polarized elongation of root hair cells. ROS home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…These proteins also show some crosstalk with different phytohormones (Masucci and Schiefelbein 1994, 1996, Kubenova et al 2022, Sun et al 2022). Additionally, abnormal ROS accumulation in RHs triggers either exacerbated growth or cell bursting, reinforcing the notion that an apoplastic and cytosol ROS‐homeostasis is required to modulate RH initiation and cell elongation by affecting cell wall properties (Orman‐Ligeza et al 2016, Pacheco et al 2022, Zhang et al 2022). The cell wall, a dynamic structure, determines the fate and shape of epidermal cells and root hairs.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…These proteins also show some crosstalk with different phytohormones (Masucci and Schiefelbein 1994, 1996, Kubenova et al 2022, Sun et al 2022). Additionally, abnormal ROS accumulation in RHs triggers either exacerbated growth or cell bursting, reinforcing the notion that an apoplastic and cytosol ROS‐homeostasis is required to modulate RH initiation and cell elongation by affecting cell wall properties (Orman‐Ligeza et al 2016, Pacheco et al 2022, Zhang et al 2022). The cell wall, a dynamic structure, determines the fate and shape of epidermal cells and root hairs.…”
Section: Introductionmentioning
confidence: 64%
“…RHs are elongated several hundred‐fold of their original dimensions in a short‐term period, and their differentiation and elongation rates are determined by both cell‐intrinsic factors and external environment signals (Bruex et al 2012, Chang et al 2021, Fedoreyeva et al 2022, Li et al 2022). The distinctive morphological characteristic and development profile of RHs make them important regulators of mineral and water uptake, especially in response to nutrient deficiencies such as phosphorus, iron, and calcium (Bates and Lynch 1996, Kohli et al 2022, Xue et al 2022, Ying and Scheible 2022, Zhang et al 2022). Genetic and molecular approaches have identified several hormones, including auxin, ethylene, jasmonic acid (JA), and abscisic acid (ABA), as important factors in RH development (Lee and Cho 2013, Rymen et al 2017, Qiu et al 2021, Li et al 2022, Martin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…ROS can be toxic to cells, however, they also play regulatory roles in numerous physiological processes, for example, in cell growth, cell division, differentiation and development, as well as responses to biotic and abiotic stimuli (Czarnocka and Karpinski, 2018; Foyer and Noctor, 2016). It has been demonstrated that ROS act as signalling molecules in the regulation of processes like pollen germination and tip growth of pollen tubes (Liu et al, 2009; Maksimov et al, 2018; Pasqualini et al, 2015; Speranza et al, 2012) as well as root hairs (Carol and Dolan, 2006; Carol et al, 2005; Foreman et al, 2003; Zhang et al, 2022). In this connection, ROS are endogenously generated by cellular NADPH oxidases (NOX) (Figure 3) (Cardenas et al, 2006; Foreman et al, 2003; Kaya et al, 2015; Kaya et al, 2014; Kaya et al, 2019; Lassig et al, 2014; Potocky et al, 2007).…”
Section: The Role Of Reactive Oxygen Species In Ir‐hormesismentioning
confidence: 99%
“…Zhang et al reported that CsRbohD is essential in resistance to cold stress in cucumber. These results suggest that RBOHD and RBOHF act as ROS signal initiators and activate antioxidant systems during plant resistance to salt and cold stress [ 36 ]. Whether RBOH D and E genes expression is regulated by other abiotic stresses and what the roles of other RBOH s are in abiotic stresses may remain to be explored.…”
Section: Ros Metabolism Under Abiotic Stressmentioning
confidence: 99%
“…Many studies have shown that exogenous Ca 2+ is beneficial for plants in scavenging ROS [ 178 , 179 , 180 ]. In general, exogenous calcium stimulates the production of ROS, which acts as a signal to activate the ROS scavenging system in plants to avoid oxidative damage [ 36 ]. Calcium ions enhance RBOH activity and promote the production of plasma membrane ROS, which act as a signal to activate antioxidant enzymes (i.e., POD, CAT and SOD) and the antioxidant system of the AsA-GSH cycle in potato tuber [ 181 ].…”
Section: The Mechanism By Which Exogenous Substances Regulate Ros Met...mentioning
confidence: 99%